СLINICAL FEATURES, DIAGNOSIS AND TREATMENT OF PATIENTS WITH RETINAL DETACHMENT DUE TO ACUTE RETINAL NECROSIS - S. V. Sdobnikova; N. R. Marchenko; N. A. Troitskaia; Z. V. Surnina; L. S. Pateyuk (Oftalʹmologiâ)
This article deals with the PCR diagnostic results of the vitreous and retina biopsy material in patients suffering from panuveitis with retinal detachment. Rhegmatogenous retinal detachment with partial hemophthalmia was diagnosed as a result of primary diagnosis. The pair eyes were intact. Ultrasound B-scan, electrophysiological studies, ocular fundus photoregistration and standard ophthalmological examination was conducted for all patients. As a special method of investigation, PCR diagnostics of a biopsy material from a primary vitrectomy was used as a special method. In ten patients with panoveitis, acute retinal necrosis and retinal detachment, vitrectomy with endolaser coagulation of the retina and a silicone tamponade was performed. Vitrectomy with endolaser retinal photocoagulation and silicone oil tamponade was performed in ten cases of panuveitis with acute retinal necrosis and retinal detachment; postoperatively systemic antiviral therapy was administered for 6–12 weeks. In the postoperative period, all patients underwent a course of systemic antiviral therapy with valaciclovir 500 mg twice a day for 6-12 weeks. In the absence of effect, valganciclovir 900 mg twice daily for 21 days was additionally used. As a result of PCR-diagnostics mixed infection (in the biopsy of the retina — viral DNA, in the biopsy of the vitreous body — DNA of the mycobacterium tuberculosis) was detected in 2 patients with the most severe retinal necrosis and panoveitis with funnel-shaped retinal detachment, Viral DNA was found in the retina biopsy specimen in one patient, and in the vitreous biopsy specimen DNA of the pathogen was not detected. Early primary vitrectomy promotes the most functional results: best corrected visual acuity after removal of the silicone oil reached 0,3–0,6 in the Golovin-Sivtsev table. The obtained data had shown, PCR is the most informative method for determining the etiology of the process is PCR diagnostics of the retina biopsy that with panoveitis with acute retinal necrosis. A potential cause of this nosological form is a mixed infection, namely, the combination of the viral nature of the disease with tuberculosis, although it is not always possible to identify all etiological agents.